Pengembangan video animasi powtoon sebagai media pembelajaran linguistik jarak jauh - Fithriyah Nurul Hidayati; Nor Laili Fatmawati (JINoP (Jurnal Inovasi Pembelajaran), 2022)
Learning media innovation is important to support student learning success, one of which is the development of Powtoon media. This study aims to develop distance learning media in the form of animated Powtoon videos that will be used to visualize linguistic phenomena in society in linguistic learning and examine the level of feasibility. Research and Development is carried out using the ADDIE model which consists of stages of analysis, design, development and implementation, stage I revision, and evaluation. This activity was carried out by testing on 30 respondents with the aim of testing the revised product according to expert input to test the readiness of the product to be used in learning Linguistics in distance classes. This research and development resulted in 13 animated videos which were used as Linguistics learning media. Aspects of material, visual communication, accessibility and benefits were assessed as Very Appropriate by material experts, media experts, and respondents in small group and large group trials, with an achievement value of 95.2%. This value is obtained from the calculation of the results of the questionnaire which is then compared with the product feasibility table which is used as a guide for the final results in this research and development.